Analysis of Sn Behavior During Ni/GeSn Solid-State Reaction by Correlated X-ray Diffraction, Atomic Force Microscopy, and Ex-situ/In-situ Transmission Electron Microscopy. (8th September 2020) - Quintero, Andrea; Gergaud, Patrice; Hartmann, Jean-Michel; Delaye, Vincent; Bernier, Nicolas; Cooper, David; Saghi, Zineb; Reboud, Vincent; Cassan, Eric; Rodriguez, Philippe
Abstract : A comprehensive study of the impact of Sn content on the Ni/GeSn phase sequence, the morphological and electrical properties evolution during the solid-state reaction (SSR) has been performed. The phase sequence was monitored by in-situ X-ray diffraction. These results were complemented by atomic force microscopy and sheet resistance measurements together with transmission electron microscopy imaging and energy-dispersive X-ray spectroscopy applied to specimens annealed both ex-situ and in-situ. The phase formation and Sn behavior during the solid-state reaction was followed. Sn segregation around grain boundaries hampered atom diffusion, delaying the growth of the Ni(GeSn) phase. In addition, a correlation between the Sn content and the morphological and electrical properties degradation has been observed.